The Characters and Mechanism Research of Hydrogen Absorption/Desorption Kinetics for Alloy Hydrogen Storage Materials (Global Journal of Science Frontier Research, 2023)
The characters of hydrogen absorption desorption kinetics for alloy hydrogen storage materials have been summarized For searching the nature of hydrogen absorption desorption kinetics the experimental research results of evolution of the phase structure during hydrogen absorption desorption processes have been summarized It is found that hydrogen storage host is hydride for Mg system alloys and is hydrogenation solid solution for Ti and rare-earth systems The situation of atom close packing and the number of interstitial sites as well as size of interstitial space of hydrogen storage materials were compared The crystallographic behaviors in hydrogen absorption desorption processes have been expounded The characters of hydrogen storage kinetics for alloy hydrogen storage materials were qualitatively explained from the thermodynamics of crystallographic behaviors Under appropriate hydrogen pressure and different temperature characters of hydrogen absorption kinetics curves are 1 The hydrogen absorption rate of initial stage and saturation quantity of hydrogen absorption increase with temperature increase for the materials Mg system that the host of hydrogen absorption is the hydride 2 The hydrogen absorption rate of initial stage and saturation quantity of hydrogen absorption decrease with temperature increase for the materials Ti and rare-earth systems that the host of hydrogen absorption is the hydrogenation solid solution
Keywords: alloy hydrogen storage material; character of hydrogen storage kinetics